Robust and brittle secured video for IOT - Lakshmi Narayanan, K; P. Ramesh, G; Divya, V (International Journal of Engineering and Technology, 2018)
In this paper the system is mainly designed for theÂ  military purpose security since now-a-days securing our military has become a difficult task .our live is mainly dependent on other objects mainly we are computer based living and digital image processing plays a vital role in it. This process has much advantage as well as some disadvantage. A VLSI circuit is built with many millions of IC chip, so it is considered to be indivisible for the construction purpose. The internet-of things (Iot) is a electronic device which is connected to the vehicle and the building item which is used to generate many secured techniques which is connected with the software, electrical, electronics and mechectronics devices and human recourses also. Better Portable Graphics Algorithm with a Context-Adaptive Binary Arithmetic Coding (CABAC) encoding algorithm is used in the existing system this process is affected by the Gaussian noise, low compression ratio and time delay to overcome above issues andÂ  enhanced with Secure Better Portable Graphics (SBPG) compression algorithm with HEVC is present .The proposed architecture is suitable for high performance imaging in the Iot and for the high quality compression files and secured transformation of image and video captured in the digital camera. Encryption and watermarking are the two technique used in the process. The watermarking technique is more secure than the previous system. This process produces high quality JPEG, and high PSNR ratio. The scrambling algorithm is used in the encryption process. It is used for providing secured image.
Keywords: .